PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN DAN DIVIDEND PAYOUT RATIO TERHADAP PERATAAN LABA (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2018) - Jayanti Fitri; Kamaliah Kamaliah; Kurnia Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of this study was to determine the effect of profitability, leverage, company size and dividend payout ratio on income smoothing. The population of this research is manufacturing companies listed on the Indonesian stock exchange in 2015- 2018. The sample selection method was carried out by purposive sampling, namely the method of selecting samples with certain criteria. Samples that fit the criteria totaled 64 companies with an observation period of 4 years so that the research sample was 256 companies. The results showed that profitability has an effect on income smoothing with a significance value of 0.008 <0.05. Company size has an effect on income smoothing with a significance value of 0.002 <0.05. The dividend payout ratio has an effect on income smoothing with a significance value of 0.003 <0.05. Meanwhile, leverage has no effect on income smoothing with a significance value of 0.170> 0.05.Keywords: Income Smoothing, Profitability, Leverage, Company Size and Dividend Payout Ratio